Social media usage among pre-service secondary mathematics teachers in Zambia - Mulenga, Eddie Mumba; Marbàn, José María (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2020)
Social media technologies have reshaped our lives today and Zambian teachers do a massive use of smart phones, tablets, and other portable tools. In addition, they are continually searching for forefront innovations. Frequently, the utilization of these gadgets is not in manners foreseen by innovation advocates. This study focuses on exploring the use of social media platforms and the impact of such social networking services in the teaching and learning of mathematics by pre-service teachers. To explore pre-service teachers’ use of social media in their teaching and learning experiences, the authors administered an adapted and validated research instrument via a quantitative survey system to a sample of 102 pre-service teachers from the Copperbelt University. Analysis of variance and multiple regression analysis were used to test the interplay of relationships between pre-service teachers’ attitudes towards the use of social media based on year of study and gender, social media use and classroom integration, social media use, and mathematics pedagogy. Further, a statistical test was run to show whether positive correlations existed or not. Results disclosed that respondents showed an average use of social media tools in mathematics and provide a prediction model for pre-service teachers’ future integration of social media in the teaching and learning of mathematics.